Dye Laser to Treat an Arteriovenous Malformation of the Tongue: 40-Month Follow-Up - Niccolò Giuseppe Armogida; Luigi Esposito; Elena Calabria; Mariangela Cernera; Gianrico Spagnuolo; Flavia Iaculli (Case Reports in Dentistry)
Arteriovenous malformations (AVMs) are abnormal connections between blood vessels that bypass the normal capillary bed. To avoid the invasiveness of the gold standard surgical excision, the use of dye laser has been suggested as an alternative. A 53-year-old man in good overall health presented with a large bluish-red nodular growth covered by intact mucosa on the left side of his tongue. The growth had a hard-elastic consistency and was not painful to touch. Imaging investigations revealed a capsulated growth consistent with a diagnosis of AVM. The patient underwent two sessions of rhodamine dye laser treatment using the following parameters: fluence of 12 J/cm2, 6 mm laser spot, a single pulse with repetition up to 1.0 Hz, and a pulse duration of 3.0 ms. Follow-up examinations were conducted at 12, 24, 36, and 40 months after the treatment. At the 40-month follow-up, the lesion had reduced in size, with a more organized vascular network, and was not clinically detectable. Considering the limitations of this case report, the application of dye laser appears to be a potentially successful treatment option for AVMs.